Depression, anxiety, stress, and dry eye disease among Gazan undergraduate health sciences and nursing students: a structural equation modeling study - Aljarousha, Mohammed; Che Azemin, Mohd Zulfaezal; Ariffin, Indang Ariati; Alhoot, Mohammed Abdelfatah; Elmanama, Abdelraouf A.; Alsaqqa, Hatem H.; Aljeesh, Yousef; Awg Isa, Mohd Zaki; Ang, Mia Yang; Alghamdi, Waleed M.; Ahmad Mizher, Hussam Abdeljabar; Shaqoura, Emad I.H. (Elsevier B.V., 2026)
Purpose: To investigate associations between dry eye disease (DED) symptoms and psychological distress (depression, anxiety, stress) among undergraduate health sciences and nursing students in the Gaza Strip during the 2023–2025 conflict period. Methods: A cross-sectional study used convenience sampling via WhatsApp and face-to-face interviews between 4 February and 29 April 2025. Participants completed a demographic form, the Arabic Ocular Surface Disease Index (OSDI), and the Arabic Depression Anxiety Stress Scale-8 (DASS-8). Analyses included descriptive statistics, group comparisons, correlations, and structural equation modeling (SEM) with interaction terms; sex was included as a covariate, and academic year was examined as an exploratory moderator of distress–symptom associations. Results: Data from 282 students (190 female, 92 male) were analyzed. OSDI scores were skewed upward (median 25.0, IQR 16.67–33.33). Using OSDI > 12, symptomatic DED prevalence was 87.9 %. OSDI correlated with depression (r = 0.37), anxiety (r = 0.44), and stress (r = 0.56), all p < 0.001. SEM indicated a stronger unique association for stress and a smaller, significant association for depression; moderation by academic year was not statistically significant. The classifier achieved good discrimination for symptomatic status (AUC = 0.829). Conclusion: Among Gazan health sciences and nursing students, DED symptoms were common and associated with psychological distress—particularly stress and, to a lesser extent, depression. Sex and academic year did not show robust effects. Findings support considering mental health within DED management for students in conflict settings.